ELECTROCHEMICAL BEHAVIOR OF ELECTROLYTES BASED ON DIMETHYLSULFONE SOLVATES: UDC 544.354.5 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
Electrochemical properties of electrolytes with solvates as ionogenic component are investigated. The method of lithium salts solvates with dimethylsulfone receipt and cleaning is developed. Work of lithium-ion accumulators models is shown with the use of the developed electrolytes.
Keywords: -